PENERAPAN MODEL SCRAMBLE PADA MATERI JENIS-JENIS PEKERJAAN UNTUK MENINGKATKAN HASIL BELAJAR SISWA Kelas IV MIN 17 PIDIE - Zahrina (JURNAL EKSPERIMENTAL : Media Ilmiah Pendidikan Guru Madrasah Ibtidaiyah, 2020)
The aim of the research was to identify whether the learning model Scramble could increase the students’ learning outcomes in the learning topic : ‘Kind of Jobs’. The type of research was Classroom Action Research (CAR). The subject were 23 students of fourth grade of MIN 17 Pidie year 2019/2020. The technique of data collection were observation, test and interview. The findings indicated-the average values in each cycle. The avarege value in cycle I was 59. 56, while the classical achievement was 34. 79%; cycle II the average value was 77.39 while the classical achievement was 65.20%; cycle III the average value was 93.04 while the classical achievement was 100%. Therefore, the implementation of Scramble could increase the learning outcomes of fourth grade students of MIN 17 concerning the learning topic : Kind of Jobs.